2018
DOI: 10.1292/jvms.17-0596
|View full text |Cite
|
Sign up to set email alerts
|

The effects of saline water consumption on the ultrasonographic and histopathological appearance of the kidney and liver in Barki sheep

Abstract: The objective of this study was to evaluate the impact of varying degrees of water salinity on the ultrasonographical and histopathological appearance of the liver and kidneys in Barki sheep. Thirty Barki sheep (initial weight, 29.48 ± 0.81 kg) were allocated into three groups (n=10 per group) based on the type of drinking water for 9 months: the tap water (TW) group (350 ppm total dissolved solids [TDS]); the moderate saline water (MSW) group (4,557 ppm TDS); and the high saline water (HSW) group (8,934 ppm T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The values did not, however, exceed the reference range ( Omidi-Mirzaei et al, 2018 ). When comparing normal drinking water, moderate saline drinking water (0.5%) and high saline drinking water (0.9%), Ghanem et al (2018) found the same result in Barki sheep. Similarly, the salinity (1.35–1.45%) of drinking water had a substantial impact on AST and ALT in sheep and camels ( Assad and El-Sherif, 2002 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The values did not, however, exceed the reference range ( Omidi-Mirzaei et al, 2018 ). When comparing normal drinking water, moderate saline drinking water (0.5%) and high saline drinking water (0.9%), Ghanem et al (2018) found the same result in Barki sheep. Similarly, the salinity (1.35–1.45%) of drinking water had a substantial impact on AST and ALT in sheep and camels ( Assad and El-Sherif, 2002 ).…”
Section: Discussionsupporting
confidence: 54%
“…In group 1, when a higher concentration of saline water (1.2%) drunk by the goats for a longer period, serum creatinine levels were higher and remained above the upper limit of the reference range ( Jackson and Cockcroft, 2002 ), suggesting that prolonged intake of saline water had adverse effects on renal function. Similarly, Ghanem et al, (2018) reported that drinking saline water (0.5–0.9%) substantially increased creatinine levels in Barki sheep. When goats were given the option of fresh or saline water again in the sensitivity re-test phase of the experiment, Runa et al, (2020) found the highest concentration of serum creatinine.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, water quality in semi-arid areas is not good for consumption. Research from [14] reported that drinking water consumption in sheep was influenced by the level of cleanliness and freshness of the water given. It is reinforced by the opinion of [15] that water quality greatly affects the level of water consumption, but each sheep has its own adaptation characteristics to the water consumed.…”
Section: Water Consumptionmentioning
confidence: 99%
“…The number of research that focused on the consequence of intake of saline water on small ruminants used NaCl added to freshwater. (Yous and Ben Salem, 2017;Castro et al, 2017;Paiva et al, 2017;Ghanem et al, 2018;Vosooghi-Postindoz et al, 2018). Also, diluted seawater has been used in a few experiments (Assad and El-Sherif, 2002;Attia-Ismail et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several research that focused on the consequence of intake of saline water on small ruminants used NaCl added to freshwater [ 9 , 10 , 11 , 12 , 13 ]. Also, diluted seawater has been used in a few experiments [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%